2009
DOI: 10.3945/ajcn.2009.27477
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin A supplementation interact with routine vaccinations? An analysis of the Ghana Vitamin A Supplementation Trial

Abstract: Background: The World Health Organization recommends vitamin A supplementation (VAS) at vaccination contacts after 6 mo of age to reduce mortality. However, it is unknown whether the effect of VAS is independent of vaccinations. One of the original VAS trials from Ghana had collected vaccination information. Objective: We reanalyzed the data to explore the hypothesis that VAS reduces mortality in children who had bacille Calmette-Guérin or measles vaccine as their most recent vaccine but increased mortality wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…41 That has turned out to fit the data perfectly including trials of VAS showing that VAS was associated with increased mortality for girls who had received DTP as their most recent vaccine. 32,42,43 Such consistencies in observational studies and corroboration of unexpected deductions are not found unless biological causality when measles vaccine was introduced in general campaigns in Senegal in the late 1980s, female-male mortality, which had not been different before the MV campaigns, in two demographic surveillance areas dropped much more for girls than boys such that girls had 35% lower mortality than boys after the campaigns. 13,14 This differential effect has been consistent in subsequent studies.…”
Section: What Can Be Done To Prove Nse?mentioning
confidence: 99%
See 1 more Smart Citation
“…41 That has turned out to fit the data perfectly including trials of VAS showing that VAS was associated with increased mortality for girls who had received DTP as their most recent vaccine. 32,42,43 Such consistencies in observational studies and corroboration of unexpected deductions are not found unless biological causality when measles vaccine was introduced in general campaigns in Senegal in the late 1980s, female-male mortality, which had not been different before the MV campaigns, in two demographic surveillance areas dropped much more for girls than boys such that girls had 35% lower mortality than boys after the campaigns. 13,14 This differential effect has been consistent in subsequent studies.…”
Section: What Can Be Done To Prove Nse?mentioning
confidence: 99%
“…36 Third, we have shown repeatedly that girls have higher mortality than boy after DTP vaccination as the most recent vaccine. 34,36,38,39,42,44 Fourth, given the sexdifferential effect of DTP, we tested the hypothesis that the problem of increased female mortality after HTMV was due to a change in the sequence of vaccinations. HTMV was given early at 4-5 months of age and most children received DTP after HTMV.…”
Section: What Can Be Done To Prove Nse?mentioning
confidence: 99%
“…29,30 In a reanalysis of one of the trials that reported a beneficial effect, 31 we found no effect among vaccinated children. 32 In more recent studies, we observed negative effects of VAS when provided to neonate girls who subsequently received DTP 33,34 and when provided to children who had received BCG revaccination. 35 The original trials documenting beneficial effects before the full implementation of the vaccination program 1 may therefore not reflect the effect of VAS today in the context of much higher vaccination coverage and repeated doses of VAS.…”
Section: The Effect Of Vas On Overall Mortalitymentioning
confidence: 99%
“…However, as has been seen in other studies (Benn, et al, 2005;Benn, et al, 2008;Benn, et al, 2009;Benn, et al, 2010), opposing effects were seen in boys and girls; boys had a 92% (-2-275%) increase in mortality while mortality in girls was lowered by 55% (13-76%). Hence, the assumption that providing HDVAC to children with vaccinations after 6 months of age can never have a negative effect on child mortality may not be correct.…”
Section: Current Evidence For Hdvacsmentioning
confidence: 67%